RESEARCH FOR PROFESSIONAL DEVELOPMENT - Kapko, Teedanai; Kositpimanwet, Ekkarat (Journal of Buddhist Education and Research (JBER), 2023)
This academic article is an education. "Conducting research for professional development", which is the basis of educational institution administrators who must be able to integrate the operations within the educational institution to develop a knowledge management system with various professional principles. to be efficient and effective for the organization What is important in action Management must understand the context of Techniques for managing research methods for professional development Professional Development Elements lead to research in which research in the context of professional development Emphasis on conducting inductive research. with an emphasis on qualitative research which administrators and teachers have an understanding of the distinctive context Points that should be developed in terms of administration and operations as well. It is therefore an important part that researchers and executives must understand the meaning, roles, components and clear design. To lead to integration and use within the organization of education effectively and create good effectiveness for the organization.